Cardiac evaluation for end-stage kidney disease patients on the transplant waitlist: a single-center cohort study - Vijayan, Swati (2023)
Background: Cardiac evaluation before deceased donor kidney transplant (DDKT) remains a matter of debate. Data on Asian countries and countries with prolonged waiting times are lacking. This study aimed to assess the outcomes of patients referred for DDKT after a cardiac evaluation at an Asian tertiary transplant center. Methods: This single-center retrospective review analyzed patients who were referred for waitlist placement and underwent cardiac stress testing between January 2009 and December 2015. Patients with cardiac symptoms were excluded. The primary outcome was three-point major adverse cardiovascular events (MACE), a composite of non-fatal myocardial infarction, non-fatal stroke, and cardiovascular death. Results: Of 468 patients referred for DDKT, 198 who underwent cardiac stress testing (myocardial perfusion studies in 159 patients and stress echocardiography in 39 patients) were analyzed. MACE occurred in 20.7% of the patients over a median follow-up of 4.6 years. Cardiac stress tests were positive for ischemia in 19.7% of the patients. Coronary angiography was performed in 63 patients, including 29 patients with diabetic kidney disease and negative cardiac stress tests. Significant coronary artery disease (CAD) was detected in 27 patients (42.8%), of whom 18 underwent revascularization. MACE was associated with significant CAD on coronary angiography in the multivariable analysis. Cardiac stress test results were not associated with MACE. Amongst diabetic patients who had negative cardiac stress tests, 37.9% had significant CAD on coronary angiography. Conclusions: The cardiovascular disease burden is significant amongst DDKT waitlist candidates. Pretransplant cardiac screening may identify patients with significant CAD at higher risk of MACE.